2021
DOI: 10.1039/d1ta03644k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in electrocatalysts and electrodes for portable fuel cells

Abstract: Fuel cells are devices that transform efficiently the chemical energy of hydrogen or another fuel into clean electricity. The fuel cells technology is attractive for its high-energy efficiency and expanded...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 497 publications
1
46
0
Order By: Relevance
“…15,16 More beneficially, favorable hydrophilic TiO 2 is conducive to the adsorption and dissociation of water molecules on its substrate surface in acid/alkaline media, generating hydroxyl species (OH) to react with CO ads on metal Pt and facilitating subsequent methanol oxidation. 17–19 Additionally, catalytic performance is also greatly related to the morphology and crystalline forms of TiO 2 . It is reported that anatase TiO 2 possessing a fraction of the rutile phase exhibited good catalytic properties compared to the individual phase.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 More beneficially, favorable hydrophilic TiO 2 is conducive to the adsorption and dissociation of water molecules on its substrate surface in acid/alkaline media, generating hydroxyl species (OH) to react with CO ads on metal Pt and facilitating subsequent methanol oxidation. 17–19 Additionally, catalytic performance is also greatly related to the morphology and crystalline forms of TiO 2 . It is reported that anatase TiO 2 possessing a fraction of the rutile phase exhibited good catalytic properties compared to the individual phase.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the overall kinetics of low-temperature fuel cells are restricted by the sluggish cathodic oxygen reduction reaction (ORR), which demands a high use level of noble metals as active sites to overcome this kinetic barrier. [1] However, the reserves of noble metals in the earth's crust are only tens of Transition metal carbides have been widely used as electrocatalyst materials in oxygen evolution, hydrogen evolution, and ORR. [35][36][37] Bimetallic carbides especially those that are synthesized at high temperature (1300-1400 °C) show a very high electrocatalytic stability and promotion effect on ORR activity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the overall kinetics of low‐temperature fuel cells are restricted by the sluggish cathodic oxygen reduction reaction (ORR), which demands a high use level of noble metals as active sites to overcome this kinetic barrier. [ 1 ] However, the reserves of noble metals in the earth's crust are only tens of thousands of tons, which is difficult to sustain. [ 2 ] Moreover, the stability of noble metal catalyst is relatively poor, further increasing the cost of fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Tackling these challenges to increase the power density, advanced materials of all components from catalysts to transport layers are required. 11,12 This work focuses on enhanced transport layers, to reduce the mass transport resistance and the related overpotential. Reducing mass transport losses will enable higher current densities and thus higher power densities can be achieved.…”
Section: Introductionmentioning
confidence: 99%